It is the time for oceanic seabirds: Tracking year‐round distribution of gadfly petrels across the Atlantic Ocean. Issue 7 (31st May 2017) - Ramos, Raül; Carlile, Nicholas; Madeiros, Jeremy; Ramírez, Iván; Paiva, Vitor H.; Dinis, Herculano A.; Zino, Francis; Biscoito, Manuel; Leal, Gustavo R.; Bugoni, Leandro; Jodice, Patrick G. R.; Ryan, Peter G.; et al.
Abstract: Aim: Anthropogenic activities alter and constrain the structure of marine ecosystems with implications for wide‐ranging marine vertebrates. In spite of the environmental importance of vast oceanic ecosystems, most conservation efforts mainly focus on neritic areas. To identify relevant oceanic areas for conservation, we assessed the year‐round spatial distribution and spatio‐temporal overlap of eight truly oceanic seabird species of gadfly petrels ( Pterodroma spp.) inhabiting the Atlantic Ocean. Location: Atlantic Ocean. Methods: Using tracking data (mostly from geolocators), we examined year‐round distributions, the timing of life‐cycle events, and marine habitat overlap of eight gadfly petrel species that breed in the Atlantic Ocean. Results: We compiled 125 year‐round tracks. Movement strategies ranged from non‐migratory to long‐distance migrant species and from species sharing a common non‐breeding area to species dispersing among multiple non‐breeding sites. Gadfly petrels occurred throughout the Atlantic Ocean but tended to concentrate in subtropical regions. During the boreal summer, up to three species overlapped spatio‐temporally over a large area around the Azores archipelago. During the austral summer, up to four species coincided in a core area in subtropical waters around Cape Verde, and three species shared habitat over two distinct areas off Brazil. The petrels used many national Exclusive Economic Zones, although they also exploited offshore international waters. Main conclusions: Tracking movements of highly mobile vertebrates such as gadfly petrels can provide a powerful tool to evaluate and assess the potential need for and location of protected oceanic areas. As more multispecies, year‐round data sets are collected from wide‐ranging vertebrates, researchers and managers will have greater insight into the location of biodiversity hotspots. These can subsequently inform and guide marine spatial planning efforts that account for both conservation and sustainable use of resources such as commercial fisheries.